Diterpenoids and C13 Nor-Isoprenoid Identified From the Leaves and Twigs of Croton yanhuii Activating Apoptosis and Pyroptosis - Li, Yue-qian; Hou, Bo-lin; Wang, Mei-jie; Wang, Ru-yue; Chen, Xiao-han; Liu, Xu; Fei, Dong-qing; Zhang, Zhan-xin; Li, Er-wei (Frontiers in Chemistry, 2022)
Croton yanhuii (Family Euphorbiaceae) is an annual aromatic plant endemic to Yunnan Province, China, which yield an aromatic, spicy oil used as a flavoring and fragrance. The aim of present study was to acquire secondary metabolites from the leaves and twigs of C. yanhuii and to evaluate their cytotoxic activity. Five new diterpenoids, croyanhuins A-E (1-5), and one new C13 nor-isoprenoid, croyanhuin F (6), were isolated from the leaves and twigs of C. yanhuii. Their structures and absolute configurations were determined by extensive spectroscopic methods (1D and 2D NMR, IR, and HRESIMS) and confirmed by electronic circular dichroism (ECD) spectra or single-crystal X-ray diffraction analysis. Among the new terpenoids, compounds 1 and 3 inhibited cell proliferation and viability in dose- and time-dependent, whereas both induced cleavage of either caspase-3 or PARP-1 in SW480 cell line. Additionally, we observed that Z-YVAD-FMK and Z-VAD-FMK, two caspase inhibitors, inhibited the compounds-depended cell viability loss, suggesting that either of them can induce pyroptosis and caspase-dependent apoptosis. These biological assay results revealed that compounds 1 and 3 induce different kind of programmed cell death in SW480 cells.